MOTIVASI PELAKSANAAN LATIHAN ROM PADA PASIEN STROKE BERDASARKAN DUKUNGAN KELUARGA DI PUSKESMAS CILEDUG KABUPATEN CIREBON - Dewi Erna Marisa (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
Stroke sufferers in the world experience disability with permanent disability 52%, mild disability as much as 23% and as many as 25% of stroke sufferers are able to avoid disability after rehabilitation. Efforts that can be made to prevent disability is to follow a rehabilitation program by doing a range of motion or called Range of motion (ROM). ROM implementation must be followed and carried out routinely so that it requires motivation from patients and that motivation can be formed with the support of the family. The purpose of this study was to analyze the motivation for implementing ROM exercises in stroke patients based on family support. Type research is a description of the correlation with cross-sectional approach. Sample uses 75 with total sampling. Data analysis using descriptive analysis and bivariate test using chi-square analysis test. Based on the results of the hypothesis test shows that the motivation to implement ROM exercises is influenced by family support. Suggestions are given to nurses to provide counseling and assistance to families so that families provide support in implementing ROM exercises